Pengaruh Modal Kerja, Total Aset, dan Pertumbuhan Penjualan terhadap Kinerja Perusahaan dengan Dimoderasi Kebijakan Hutang - Dewi Puspita; Hermanto Hermanto (Universitas Batanghari Jambi, 2023)
This study aims to understand the effect of working capital, company size, and sales growth on company performance by moderating debt policy. The data in the study is in the form of secondary data obtained from the financial statements of the food and beverage manufacturing industry listed on the Indonesia Stock Exchange (IDX) in 2018 to 2021. The study resulted in 168 data samples from 42 companies using the Purposive Sampling technique. The approach in this research uses quantitative methods and focuses on testing hypotheses through the Moderated Regression Analysis (MRA) method. Based on the studies that have been carried out, the results are that working capital affects company performance positively, company size has a negative influence on company performance and sales growth does not affect company performance, then leverage is able to moderate working capital negatively on company performance, leverage is able to moderate company size positive impact on company performance, and leverage cannot moderate the relationship between sales growth and company performance.